2016
DOI: 10.3136/fstr.22.387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Germination on the Antioxidant Capacity of Pigmented Rice (<i>Oryza sativa</i> L. cv. Superjami and Superhongmi)

Abstract: The effect of germination on the antioxidant capacity of pigmented and non-pigmented rice was investigated.The blackish purple Superjami, reddish-brown Superhongmi, and ordinary non-pigmented brown rice were germinated for 72 h. The germinated rice grains were extracted with 80% methanol and their antioxidant activities and compounds were analyzed. Germination substantially increased the free radical scavenging activity, reducing power, ferrous chelating ability, and superoxide dismutase activity in all the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Between the two Superhongmi rice-fed groups, the GSH rats exhibited a greater body weight-lowering effect and hypoglycemic activity than the SH group. Germinated rice, especially pigmented cultivar, contains substantially higher amounts of bioactive compounds than non-germinated rice [4,5,19]. In the present study, γ-oryzanol, GABA, phytic acid, tocols, and policosanol were significantly higher in a germinated rice sample than that of the non-germinated one.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Between the two Superhongmi rice-fed groups, the GSH rats exhibited a greater body weight-lowering effect and hypoglycemic activity than the SH group. Germinated rice, especially pigmented cultivar, contains substantially higher amounts of bioactive compounds than non-germinated rice [4,5,19]. In the present study, γ-oryzanol, GABA, phytic acid, tocols, and policosanol were significantly higher in a germinated rice sample than that of the non-germinated one.…”
Section: Discussionsupporting
confidence: 43%
“…Rice cultivars with colored pericarp, such as Superhongmi, are rich in antioxidant compounds such as anthocyanins, tocols, γ-oryzanol, and phytic acid [53] and germination could further increase the amount of these antioxidant compounds. Germinated Superhongmi rice has been previously reported to contain a substantial amount of antioxidant compounds and to have a strong antioxidant capacity [19]. Past investigations revealed that dietary antioxidants could prevent bone loss in postmenopausal women and ovariectomized animals and may be useful in the prevention and treatment of osteoporosis [54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GR enzyme transforms oxidized glutathione into reduced glutathione, an antioxidant [43], while PON enzyme reduces lipid peroxides and hydrolyzes oxidized phospholipids [44]. Superjami rice is rich in natural antioxidants, and germination further increases the amount of these antioxidant compounds, which may have been responsible for the enhanced antioxidant defense status in OVX rats [15]. Studies have shown that Superjami rice inhibited oxidative stress and enhanced the antioxidant enzyme activities in high fat-fed mice and that its antioxidant capacity markedly increased after germination [1,15].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dormancy enzymes are activated during rice germination, resulting in the degradation of large biomolecules and the production of bioactive substances [14]. Germination has been found to increase the quantity of antioxidant compounds and enhance the antioxidant capacity of Superjami rice [15]. Further, dietary supplementation of germinated Superjami rice has been previously shown to ameliorate the lipid metabolism and reduce the risk of dyslipidemia in menopause animal model [16].…”
Section: Introductionmentioning
confidence: 99%